Postoperative Bleeding Following Involutional Entropion Surgery in an Elderly Patient with a History of Dual Antiplatelet Therapy Use: A Case Report - Andyn Robioleny Saparin; Sukoto Sukoto (CV. Publikasi Indonesia, 2026)
Elderly patients often undergo dual antiplatelet therapy (DAPT) for cardiovascular conditions, which increases the risk of postoperative bleeding, including after involutional entropion surgery. The management of antiplatelet therapy in the perioperative period remains a clinical challenge that requires careful consideration. This case report aims to discuss the risk of severe postoperative bleeding associated with continuing DAPT during the perioperative period and to emphasize the importance of comprehensive perioperative care in elderly patients undergoing eyelid surgery. A 76-year-old man on DAPT (aspirin and clopidogrel) underwent right involutional entropion surgery. Four days postoperatively, he experienced persistent ocular bleeding requiring hospitalization. Hemoglobin decreased from 12.7 g/dL to 7.5 g/dL, while coagulation parameters remained within normal limits. The patient received a pressure dressing, systemic tranexamic acid, vitamin K, and three units of packed red blood cells. Following cardiology consultation, DAPT was discontinued. The bleeding gradually decreased and completely resolved within six days after DAPT discontinuation. The patient required seven days of hospitalization and blood transfusion due to the significant drop in hemoglobin. No further complications were observed during follow-up. Continuing DAPT during the perioperative period may cause serious postoperative bleeding, even after minor ophthalmic procedures. Careful medication review, multidisciplinary coordination, and patient education are essential to reduce bleeding risk in elderly patients undergoing entropion surgery.